David in distress: his portrait through the historical psalms - Johnson, Vivian L. (Library of Hebrew Bible/Old Testament studies, 2009)
This book analyzes the thirteen historical psalms (3, 7, 18, 34, 51, 52, 54, 56, 57, 59, 60, 63, 142) in the Psalter that refer to crucial moments in King David's life as recorded in the Samuel narrative (1 Sam 16-1 Kings 2). Because most Psalms research focuses on the original setting, the so-called Sitz-im-Leben , of these late additions to the book of Psalms, they have received little attention. Using a text-based analysis, Johnson has found that these historical psalms focus on episodes of King David's life in which he experienced trouble. For example, Psalm 3 refers to